Surveying water and wastewater management in Hospitals of Qom Province - mohamad Fahiminia; Elham Taherian; Abolfazl Mohammadbeigi (Tehran University of Medical Sciences, 2015)
Background: Hospitals have been known as main water consumers .Moreover ,  the amount of their produced  wastewater and contamination is much more than domestic subscribers. Hospital waste management has recently emerged as an issue of major concerns but wastewater produced has not received sufficient attention. As there is a separate source of drinking water from that of sanitary usage in hospitals of Qom, surveying the consumption  of water and the amount of  produced wastewater will provide a lot of information in order to estimate amount of water requirement and wastewater produced in the hospitals Materials and Methods: The amount of water consumption in hospitals had been collected from the year of 2008 to 2013. Collected data and conversion ratio of water to wastewater had been used for estimating the amount of wastewater. The data was analyzed by SPSS 19 software. Pearson correlation test was used to determine the relationships between variables. By identifying strengths and weaknesses of current system , appropriate interventions for better management of water and sewage systems were presented. Results: The average of water consumption was found to be 655.7 liter per day per bed and 8.6 liters  per square meter of substructure area among all eight hospitals surveyed.There was a statistically meaningful relationship between consumed water in hospitals and substructure area (p<0.05).The average quantity of wastewater produced was estimated as 567.6 liter per day per bed. The main method of wastewater disposal is discharge in an absorbing well. Conclusion: In order to improve the current situation of  mentioned  hospitals, reconstructing water and wastewater facilities , using  wastewater treatment packages and connecting waste water of hospitals to systems of wastewater collection of city seems inevitable.